La construcción de la ciudad como espacio público - Cortés L., Fernando (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 1996)
Brunner conceives the public space as a structural element of urbanism and the urban space. Urbanism becomes a synthesis of art, science and technology, serving the well-being of the community. It should aim at constructing a city as a harmonious, balanced work of art.